2002
DOI: 10.1159/000048992
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a High Salt Diet on Microvascular Antioxidant Enzymes

Abstract: High dietary salt intake decreases the endothelium-dependent dilation of skeletal muscle arterioles by inhibiting local nitric oxide (NO) activity without changing vascular smooth muscle responsiveness to NO. Under these conditions, microvascular walls show evidence of oxidative stress, and scavengers of reactive oxygen species (ROS) abolish this oxidative stress and restore normal arteriolar responses to acetylcholine (ACh). We tested the hypothesis that the salt-dependent appearance of microvascular ROS, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
76
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(85 citation statements)
references
References 45 publications
6
76
3
Order By: Relevance
“…This hypothesis is supported by the report of Fukai et al (6), who demonstrated that ANG II increases extracellular SOD expression in mouse aorta, both in vivo and in organoid culture. Additional support for this hypothesis is provided by the findings of other investigators, who reported that a reduction in extracellular SOD activity contributes to elevated superoxide levels and impaired flow-induced dilation in patients with chronic heart failure (13) and that reduced Cu/Zn SOD activity contributes to elevated superoxide levels and loss of arteriolar NO activity in rats on a HS diet (14). The hypothesis that oxidative stress is lower and NO-dependent relaxation is preserved to a greater extent in aortas from ANG II-infused rats fed a HS diet is supported by the results of our functional studies showing that Tempol causes less relaxation and L-NAME causes a larger contraction in aortas from ANG II-infused animals on a HS diet compared with vessels from rats on a HS diet without ANG II infusion (Fig.…”
Section: Camentioning
confidence: 83%
“…This hypothesis is supported by the report of Fukai et al (6), who demonstrated that ANG II increases extracellular SOD expression in mouse aorta, both in vivo and in organoid culture. Additional support for this hypothesis is provided by the findings of other investigators, who reported that a reduction in extracellular SOD activity contributes to elevated superoxide levels and impaired flow-induced dilation in patients with chronic heart failure (13) and that reduced Cu/Zn SOD activity contributes to elevated superoxide levels and loss of arteriolar NO activity in rats on a HS diet (14). The hypothesis that oxidative stress is lower and NO-dependent relaxation is preserved to a greater extent in aortas from ANG II-infused rats fed a HS diet is supported by the results of our functional studies showing that Tempol causes less relaxation and L-NAME causes a larger contraction in aortas from ANG II-infused animals on a HS diet compared with vessels from rats on a HS diet without ANG II infusion (Fig.…”
Section: Camentioning
confidence: 83%
“…In contrast to findings demonstrating that large elevations in Ang II levels induce hypertension and increase oxidative stress, 15,17,24 Fukai et al 26 recently reported that Ang II increases extracellular superoxide dismutase (ecSOD) activity, ecSOD mRNA, and ecSOD protein expression in mouse aorta and increases ecSOD mRNA in human aortic vascular smooth muscle cells. Other studies indicate that reduced Cu/Zn SOD activity contributes to impaired ACh-induced dilation in arterioles of normotensive rats on HS diet 10 and that Cu/Zn SOD and Mn SOD expression are reduced in the kidney of SS rats fed HS diet. 16 Overall, those findings suggest that exposure to chronically low Ang II levels during HS diet (or in SS rats on LS diet) could lead to increased oxidative stress because of downregulation of antioxidant enzymes such as superoxide dismutase.…”
Section: Discussionmentioning
confidence: 99%
“…15 Although arterial NADPH oxidase activity was suppressed in potassium-supplemented and salt-loaded DS rats compared with normal-salt diet-fed animals in this study, ROS generation from cuffed arteries was similar in these animals. Thus, NADPH oxidase-independent ROS-producing or -scavenging systems, eg, mitochondrial ROS generation 30 and microvascular superoxide dismutase, 31 which have been reported to be stimulated by salt loading but might not be inhibited by dietary potassium, may also contribute to ROS production in cuffed arteries of salt-loaded DS rats.…”
Section: Discussionmentioning
confidence: 99%